CBMS-01 Mechanism of brain tumor malignancy caused by aging and social isolation. (28th November 2020) - Yamashita, Daisuke; Flanary, Victoria; Yamaguchi, Shinobu; Ohtsuka, Yoshihiro; Ozaki, Saya; Suehiro, Satoshi; Inoue, Akihiro; Gorospe, Myriam; Nakano, Ichiro; Kunieda, Takeharu
Abstract: The rise in population aging worldwide is causing an unparalleled increase in death from many cancers, including glioblastoma (GBM). In advanced countries, the number of elderly people living alone is increasing due to the rapid aging of the population and the socialization of nuclear families. Here, we explored the impact of aging and social isolation on GBM tumorigenesis. In normal brain tissue, aging promoted pathways related to cytokines and inflammation, which were further promoted by social isolation. In tumor tissues, the expression of neuron/synapse-related genes was significantly reduced in aged mice, and their expression was further reduced by social isolation. In addition, the survival period of aged mice was significantly shorter than that of young mice, and the survival period was further shortened by social isolation, which was characteristic of males. This phenomenon was the same in humans, and the survival period in the young group was significantly longer than that in the elderly group, and in the elderly group, the survival period was shortened in the male elderly group living alone. Our data indicate that social isolation contributes to the highly aggressive GBM by the shift to neuro-inflammation in the elderly brain.